2003
DOI: 10.1038/sj.bjp.0705242
|View full text |Cite
|
Sign up to set email alerts
|

P2Y receptor regulation of cultured rat cerebral cortical cells: calcium responses and mRNA expression in neurons and glia

Abstract: 1 We have investigated increases in cytosolic Ca 2+ in response to nucleotides in mixed rat cerebrocortical cultures (neurons and glia in similar numbers) and in essentially neuron-free glial cultures. 2 In both cultures, the agonist-response profile was 2-methylthioADP(2MeSADP)42-methylthioATP(2MeSATP)4ADP4ATP4adenosine 5 0 -O-(3-thiotriphosphate), consistent with a P2Y 1 receptor. The maximal responses to 2MeSADP, 2MeSATP and ADP were identical, but that to ATP was higher. 3 Suramin, pyridoxal-phosphate-6-az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…22,30,62 Although DRG neurons respond to high-K ϩ with a rapid increase in intracellular Ca 2ϩ , glia in these cultures do not; therefore this stimulus can also be used as a marker for neuronal cells. 6,17,40 We found that high-K ϩ (40 mmol/L)-evoked depolarization of DRG neurons initiates a reversible and reproducible increase in intracellular Ca 2ϩ (Fig 4D). Pilot experiments showed an attenuation of high-K ϩ -evoked Ca 2ϩ responses at pH e 6.1 and pH e 6.5, consistent with reports in the literature, 15,26 and we therefore chose to assess morphine inhibition at pH e 7.6, pH e 7.2, and pH e 6.8.…”
Section: Morphine Inhibition Of High-k ؉ -Induced Ca 2؉ Responsesmentioning
confidence: 81%
“…22,30,62 Although DRG neurons respond to high-K ϩ with a rapid increase in intracellular Ca 2ϩ , glia in these cultures do not; therefore this stimulus can also be used as a marker for neuronal cells. 6,17,40 We found that high-K ϩ (40 mmol/L)-evoked depolarization of DRG neurons initiates a reversible and reproducible increase in intracellular Ca 2ϩ (Fig 4D). Pilot experiments showed an attenuation of high-K ϩ -evoked Ca 2ϩ responses at pH e 6.1 and pH e 6.5, consistent with reports in the literature, 15,26 and we therefore chose to assess morphine inhibition at pH e 7.6, pH e 7.2, and pH e 6.8.…”
Section: Morphine Inhibition Of High-k ؉ -Induced Ca 2؉ Responsesmentioning
confidence: 81%
“…The P2Y 1 R is well established to be in the family of G q/11 -linked receptors and thus is expected to signal upon agonist activation primarily via phospholipase C, inositol trisphosphate, and mobilization of Ca 2ϩ from intracellular stores (Abbracchio et al, 2006). With rat cortex mixed-cell cultures, Bennett et al (2003) found that only 9 to 15% of the neurons mobilized Ca 2ϩ in response to P2Y 1 R agonists (but all glia did so) in testing at an earlier stage than ours (E14 cortex, cultured only for 8 days, and with ϳ50% glia present). Therefore, our cortex cultures, being more mature and with glial suppression, were compared here in this response.…”
Section: Resultsmentioning
confidence: 99%
“…This extends the previous findings on P2Y 1 R mRNA in the cortex. Thus, Moore et al (2001) found it is strongly expressed in total extracts of the adult human cortex, and Bennett et al (2003) showed that it is abundant in extracts of E14 rat cortex and in mixed-cell cultures derived from it, and in glia cultured alone. Specifically, in the multiprocess-bearing astrocytes freshly isolated from the rat cortex or hippocampus, 10 to 30% of the cells have been found to contain P2Y 1 R mRNA and to show P2Y 1 R functional responses, with this proportion increasing to ϳ90% of astrocytes after 2 weeks in culture (Zhu and Kimelberg, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…sion molecularly with selective siRNAs, strongly supporting our notion that P2Y 1 R mediates the protective effect of ATP. Several studies have shown that the expression level of P2Y 1 R in astrocytes changes under different culture conditions and is different in different tissues of origin (Bennett et al, 2003;Cheung et al, 2003;Pearce and Langley, 1994;Kimelberg, 2001, 2004). However, ATP could also prevent the cell death of astrocytes via activation of P2Y 1 R in hippocampal cultures, as well as in forebrain astrocyte cultures.…”
Section: Discussionmentioning
confidence: 99%